ALIRAN SAKSI YEHUWA DI M ARPOYAN DAMAI PEKANBARU RIAU - Manullang, Atok Daniel; Rosaliza, Mita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The background of this research comes from the author's observation of the existence of Jehovah's Witnesses in Riau Marpoyan Damai Riau. The purpose of this study is to foster the development of knowledge about religious schools, especially in the Marpoyan Damai area of Riau Pekanbaru. The theory used is the Functional Theory of Religion proposed by Emile Durkheim which consists of Trust, Ritual and Community. This type of research uses a descriptive qualitative approach using the Purspossive Sampling method. The subjects of this study were 7 people consisting of 5 informants and 2 key informants. Data collected with data collection techniques in the form of observation and interviews. Analysis of the data used in this study with the technique of collecting data from various sources by including the source of the theory used in accordance with social phenomena. The results of this study were that Jehovah's Witnesses entered the Pekanbaru in 1968 brought by Frank Race. And for the total number of Jehovah's Witnesses per 2019 there were around 350 people. The doctrine carried out by Jehovah's Witnesses varied greatly from: spreading printed material (magazines), visits to buyers, lessons at home, regional lessons, invited to the royal hall, candidates sent as sellers, candidates sent to the theocracy. Keyword: The Flow of Jehovah's Witnesses, The doctrine, History and Existence.